New diagnostic criteria and severity assessment of acute cholecystitis in revised Tokyo guidelines - Yokoe, Masamichi; Büchler, Markus W. (Journal of hepato-biliary pancreatic sciences, 2012)
Background The Tokyo Guidelines for the management of acute cholangitis and cholecystitis (TG07) were published in 2007 as the world's first guidelines for acute cholangitis and cholecystitis. The diagnostic criteria and severity assessment of acute cholecystitis have since been widely used all over the world. A validation study of TG07 has shown that the diagnostic criteria for acute cholecystitis are highly reliable but that the definition of definite diagnosis is ambiguous. In addition, considerable new evidence referring to acute cholecystitis as well as evaluations of TG07 have been published. Consequently, we organized the Tokyo Guidelines Revision Committee to evaluate TG07, recognize new evidence, and conduct a multi-center analysis to revise the guidelines (TG13). Methods and materials We retrospectively analyzed 451 patients with acute cholecystitis from multiple tertiary care centers in Japan. All 451 patients were first evaluated using the criteria in TG07. The “gold standard” for acute cholecystitis in this study was a diagnosis by pathology. The validity of TG07 diagnostic criteria was investigated by comparing clinical with pathological diagnosis. Results Of 451 patients evaluated, a total of 227 patients were given a diagnosis of acute cholecystitis by pathological examination (prevalence 50.3 %). TG07 criteria provided a definite diagnosis of acute cholecystitis in 224 patients. The sensitivity of TG07 diagnostic criteria for acute cholecystitis was 92.1 %, and the specificity was 93.3 %. Based on the preliminary results, new diagnostic criteria for acute cholecystitis were proposed. Using the new criteria, the sensitivity of definite diagnosis was 91.2 %, and the specificity was 96.9 %. The accuracy rate was improved from 92.7 to 94.0 %. In regard to severity grading among 227 patients, 111 patients were classified as Mild (Grade I), 104 as Moderate (Grade II), and 12 as Severe (Grade III). Conclusion The proposed new diagnostic criteria achieved better performance than the diagnostic criteria in TG07. Therefore, the proposed criteria have been adopted as new diagnostic criteria for acute cholecystitis and are referred to as the 2013 Tokyo Guidelines (TG13). Regarding severity assessment, no new evidence was found to suggest that the criteria in TG07 needed major adjustment. As a result, TG07 severity assessment criteria have been adopted in TG13 with minor changes.